Characterization and application of cerium fluoride film in infrared antireflection coating - Su, Wei-tao; Li, Bin; Liu, Ding-quan; Zhang, Feng-shan (Infrared physics & technology, 2009)
Cerium fluoride (CeF 3) thin films were evaporated to the germanium substrates at different substrate temperature from 100 °C to 250 °C. Structural and optical properties were characterized by X-ray diffraction (XRD), scan electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The morphology of samples deposited at different temperature can be closely related to preferred orientation. The infrared optical constants were obtained by fitting the transmission spectrum using Lorentz oscillator model. A simple example for fabrication of long-wave infrared broadband antireflection coating was also presented.